2012
DOI: 10.1136/jnnp-2012-302729
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and genetic architecture of focal primary torsion dystonia

Abstract: Of all of the FPTD patients, 25% had a familial predisposition; in 2.4% a Mendelian inheritance pattern was noted. With a stronger family history, a significantly lower AaO was seen in all focal dystonias. In both the sporadic and familial focal dystonia groups, AaO had an effect on the distribution of dystonia, with a caudal to cranial tendency. In all focal dystonia forms, women were more frequently affected, except for writer's cramp. Careful clinical characterisation will allow the formation of phenotype s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…The reported prevalence of sensory tricks was similar to that found in previous studies [28,46]. The physiology of such alleviating manoeuvres in dystonia has been suggested to involve modulation of abnormally increased facilitation [47,48]; detailed characterization of the neurophysiological mechanisms of such alleviating manoeuvres would contribute to increased understanding of sensorimotor integration in dystonia.…”
Section: Sensory Trickssupporting
confidence: 83%
See 2 more Smart Citations
“…The reported prevalence of sensory tricks was similar to that found in previous studies [28,46]. The physiology of such alleviating manoeuvres in dystonia has been suggested to involve modulation of abnormally increased facilitation [47,48]; detailed characterization of the neurophysiological mechanisms of such alleviating manoeuvres would contribute to increased understanding of sensorimotor integration in dystonia.…”
Section: Sensory Trickssupporting
confidence: 83%
“…A family history of dystonia in these remaining 19 patients cannot be confirmed; Leube and colleagues suggest that patient report is likely to significantly underestimate actual rates of dystonia amongst family members [6]. Reported rates of family history of dystonia in seemingly sporadic AOIFD vary from 26.1% [53], 18% [6] to 9.1% [28]. The patterns of inheritance observed in this study would support an autosomal dominant transmission of genes predisposing to dystonia, with reduced penetrance.…”
Section: Genetic Aspectsmentioning
confidence: 60%
See 1 more Smart Citation
“…The expression of the phenotype depends on other, as yet unknown factors, some of which may be environmental . Except for writer's cramp, women are more frequently affected in all AOPTD phenotypes . It has been suggested that (1) higher awareness of symptoms among women, (2) genetic factors, and (3) increased exposure to environmental factors are possible factors leading to the higher prevalence of focal dystonia in women .…”
Section: Discussionmentioning
confidence: 99%
“…The latter group of dystonias includes cervical dystonia, writer's cramp, blepharospasm, and spasmodic dysphonia, as well as segmental forms of dystonia. It often appears sporadic but still has relatively high heritability, for which genetic susceptibility factors or even dominantly acting genes with very low penetrance are being discussed …”
Section: What Is the Contribution Of Genetics To Dystonia?mentioning
confidence: 99%